Internalization of Moderation Values in Educational Marketing Mix Strategy Management at MI Kresna Mlilir Madiun - Yuli Umro'atin (Prodi PAI STIT Sunan Giri Bima, 2025)
MI Kresna in its history has prioritized the attitude of religious tolerance, meaning accepting all changes including the culture of society, and not discriminating against any religious organization, nor being fanatical about a particular sect, and this is what makes it continue to exist and be accepted by the wider community. This study uses a qualitative type with a case study approach, data collection through interviews, observation and documentation, data analysis through condensation, data presentation and drawing conclusions. The results of the study, namely: internalization of the value of moderation in the formulation of educational marketing mix strategies at MI Kresna Mlilir Madiun, which includes determining promotions, determining activity plans, determining educational funding, applying the value of tolerance, seeing the conditions of prospective students, being simple and not excessive in planning. Internalization of the value of moderation in the implementation of educational marketing mix strategies through creative learning activities, habituating religious activities, reflecting a moderate attitude or not being excessive/fanatical, and respecting multiculturalism in education. Internalization of the value of moderation in the evaluation of marketing mix strategies, by applying an attitude of tolerance, respect, not being excessive in attitudes and actions.